Rancangan Model Pembelajaran Paradigma Sinektika untuk Peningkatkan Keterampilan Menulis Teks Anekdot Fase E Kurikulum Merdeka - Hasnah Setiani (Lembaga Pengembangan Kinerja Dosen, 2025)
The Paradigma Sinektika learning model is a recommendation for educators to overcome the problems of learning to write literary genre texts, especially fantasy story texts with six innovative learning syntaxes. The Paradigma Sinektika Model is a development model that adopts the Suchman model and the Problem Based Learning (PBL) model. This study aims to contextually develop an innovative learning model and propose a form of implementation of the Paradigma Sinektika model in learning to write fantasy story texts. This study uses library research methods (library research). Sources of literature in research are classified into primary data and secondary data. Data collection techniques in this library research with documentation techniques. The data collection instrument was in verbal symbolic form, meaning that researchers collected texts for analysis using notes or recording devices. The data analysis technique uses the Miles and Huberman data analysis method. The results showed that the development of the Paradigma Sinektika learning model included a syntactic component consisting of six syntaxes, reaction systems, social systems, support systems, accompaniment effects and instructional impacts.